2017
DOI: 10.1007/s00204-017-1977-y
|View full text |Cite
|
Sign up to set email alerts
|

Combination of multiple neural crest migration assays to identify environmental toxicants from a proof-of-concept chemical library

Abstract: Many in vitro tests have been developed to screen for potential neurotoxicity. However, only few cell function-based tests have been used for comparative screening, and thus experience is scarce on how to confirm and evaluate screening hits. We addressed these questions for the neural crest cell migration test (cMINC). After an initial screen, a hit follow-up strategy was devised. A library of 75 compounds plus internal controls (NTP80-list), assembled by the National Toxicology Program of the USA (NTP) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 68 publications
2
47
0
Order By: Relevance
“…Several studies have shown that EGCG can bind to laminin (Peter et al, 2017;Suzuki and Isemura, 2001) and disturb the adhesion of cells to the extracellular matrix (Bracke et al, 1987;Chen et al, 2003;Suzuki and Isemura, 2001) finally leading to an altered cell migration pattern (Bal-Price et al, 2017;Barenys et al, 2017a;Nyffeler et al, 2017). The structural moieties inducing this altered cell migration seemed to be galloyl/pyrogallol groups because in a previous study, catechins lacking these residues did not disrupt cell adhesion (Barenys et al, 2017a).…”
Section: Egcg ≈ G37 > M2 > M1 ≈ G56 > Nano-egcgmentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have shown that EGCG can bind to laminin (Peter et al, 2017;Suzuki and Isemura, 2001) and disturb the adhesion of cells to the extracellular matrix (Bracke et al, 1987;Chen et al, 2003;Suzuki and Isemura, 2001) finally leading to an altered cell migration pattern (Bal-Price et al, 2017;Barenys et al, 2017a;Nyffeler et al, 2017). The structural moieties inducing this altered cell migration seemed to be galloyl/pyrogallol groups because in a previous study, catechins lacking these residues did not disrupt cell adhesion (Barenys et al, 2017a).…”
Section: Egcg ≈ G37 > M2 > M1 ≈ G56 > Nano-egcgmentioning
confidence: 92%
“…In a previous study using human and rat neurospheres we have shown that EGCG inhibits adhesion and migration of neural progenitor cells (NPCs) and that at higher concentrations it also produces a reduction of the number of migrating young neurons in vitro, without affecting NPC proliferation . An independent research group has recently reproduced these migration alteration effects in a different test model (cMINC) showing that EGCG also inhibits human neural crest cells migration in vitro (Nyffeler et al, 2017). Besides being a freely-available food-supplement, EGCG is also intensively studied at a preclinical level as a potential prenatal treatment to decrease developmental adverse effects induced by toxic substances, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…UKN2 (cMINC): Pre-differentiated neural crest cells (NCC) (Zimmer et al 2012 ) were seeded to coated multi-well plates with inserted silicon stoppers to create a cell-free area as described earlier (Nyffeler et al 2017a , b ). Cell migration was initiated one day after seeding by removal of the stopper, and test compound was added.…”
Section: Methodsmentioning
confidence: 99%
“…, ( Mundy et al, 2010 ; Radio et al, 2015 )), migration ( e.g. , ( Nyffeler et al, 2017 )), neurite outgrowth ( e.g. , ( Harrill et al, 2013 , 2015 )), synaptogenesis and neuronal network formation and function ( e.g.…”
Section: Development Of Iata-driven By Aops and Key Neurodevelopmentamentioning
confidence: 99%